1997
DOI: 10.1021/ma961297h
|View full text |Cite
|
Sign up to set email alerts
|

Dewetting Dynamics at a Polymer−Polymer Interface

Abstract: We have studied the dynamics of dewetting at the interface between polystyrene (PS) and poly(methyl methacrylate) (PMMA) as a function of the molecular weights of the two materials. Optical microscopy and atomic force microscopy have been used to follow the dewetting process and to image both the surface and interfacial structure in the vicinity of the growing holes. We determined the scaling behavior of the dewetting velocity as a function of the molecular weight of the dewetting species (PS). Different regim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
113
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(124 citation statements)
references
References 14 publications
10
113
1
Order By: Relevance
“…We use a technique developed by Qu et al 10 where we observe the rate of dewetting in polymer bilayer films and apply the theory of Brochard-Wyart et al 11 to extract the viscosity of the films. We show that even in the case where particles are well dispersed in the films, large effects on the stability of the film due to dewetting may be induced by the addition of fillers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We use a technique developed by Qu et al 10 where we observe the rate of dewetting in polymer bilayer films and apply the theory of Brochard-Wyart et al 11 to extract the viscosity of the films. We show that even in the case where particles are well dispersed in the films, large effects on the stability of the film due to dewetting may be induced by the addition of fillers.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, known as the "solidlike lower layer regime", the viscosity is given by where cos θ e ) (γ B -γ AB )/γ A . Hence, if the parameters in eq 2 are known for a given set of polymers, Qu 10 has shown that one can use eq 2 to determine the viscosity of the film. Here we use this technique to compare the effect of adding fillers into the homopolymer film's viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, much attention has been paid to the dewetting behaviour of poly(styrene) (PS) films on silicon or on another polymer [4][5][6][7][8][9][10][11][12], such as rubbery poly(dimethyl siloxane) (PDMS) [1,11,12]. In other studies, the spinodal dewetting of thin poly(methyl methacrylate) (PMMA) films deposited on a PS substrate has been extensively investigated [13,14,3].…”
mentioning
confidence: 99%
“…The ''pancake-like'' droplets evidently have anisotropic structure. The interface characteristic is similar to that of PS dewetting on PMMA surface, 11,12 although the final patterns have big differences possibly due to strong shear force from dewetting and phase separation. The AFM images indicate that the interface deformation is highly localized near the contact line.…”
Section: Resultsmentioning
confidence: 62%
“…[9][10][11][12] This report studies the phase separation and dewetting of PS and PMMA blend films with different thickness, using optical video microscopy in situ during annealing. For the first time, we report the interface characteristic of PS/PMMA in the final stage of phase separation.…”
Section: Introductionmentioning
confidence: 99%